Peanut and Soy Protein-Based Emulsion Gels Loaded with Curcumin as a New Fat Substitute in Sausages: A Comparative Study - Hong-Yan Yan; Shao-Bing Zhang (Gels)
The aim of this study was to evaluate the effects of the complete or partial substitution (0, 20, 40, and 100%) of the pork backfat in prepared sausage with protein emulsion gels loaded with curcumin. The effects of three protein emulsion gels (i.e., peanut proteins, ultrasound-modified peanut proteins, and soy proteins) on sausage characteristics (cooking loss, textural properties, microstructure, sensory characteristics, and antioxidant activity) were investigated and compared using a one-way analysis of variance and Duncan’s multiple tests. The results revealed that the addition of each emulsion gel reduced cooking loss and improved the textural properties of the sausages in a dose-dependent manner. When 20% of pork backfat was substituted with untreated or ultrasound-modified peanut protein emulsion gel (PPEG), cooking loss decreased to a greater extent than when soy protein emulsion gel (SPEG) was used. However, the latter yielded higher cohesiveness and resilience at the same substitution levels. Compared with untreated PPEG, the sausages containing modified PPEG (at 200 W for 20 min) had significantly greater resilience and a denser microstructure. In addition, when 100% of pork backfat was substituted with modified PPEG, the sausages had desirable sensory characteristics. All sausages enriched with protein emulsion gels loaded with curcumin presented higher DPPH and ABTS radical scavenging capacities than the control sausages. The sausages prepared with the modified PPEG had the highest antioxidant activity (DPPH: 37.43 ± 0.35%; ABTS: 39.48 ± 0.50%; TBARS: 0.65 ± 0.05 mg MDA/Kg), which may be attributed to the increased stability of curcumin in the modified PPEG with a denser network structure. Therefore, ultrasound-modified PPEG loaded with curcumin can be used as a new fat substitute in functional sausages or other healthy meat products.